Association between triglyceride glucose–body mass index and acute kidney injury and renal replacement therapy in critically ill patients with sepsis: analysis of the MIMIC-IV database - Wang, Shijie; Li, Ruowen; Zhang, Li; Xie, Tingbin; Wang, Xinying (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have linked kidney damage to insulin resistance (IR), yet the association between triglyceride glucose–body mass (TyG–BMI) index, a reliable marker of IR, and acute kidney injury (AKI) remains unclear.MethodsPatient data were collected from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. AKI was set as the primary endpoint, and renal replacement therapy (RRT) was set as the secondary endpoint to represent the progression of AKI. TyG–BMI index and study endpoints were analyzed using Cox regression and restricted cubic spline (RCS) analyses.ResultsA total of 1,117 patients with sepsis were enrolled, of whom 559 (50.0%) developed AKI. The result of Cox regression revealed that the TyG–BMI index was closely related to AKI (P = 0.032), and RCS analysis depicted a nonlinear correlation (P for nonlinear = 0.013). For RRT, similar results were observed. Compared with the simple severity of illness scores (SOFA, APSIII, SAPSII, and SIRS), when combined with the TyG–BMI index, their predictive ability for sepsis-related AKI significantly increased (AUCs: 0.745, 0.732, 0.708, and 0.566 vs. 0.756, 0.747, 0.728, and 0.661; all P < 0.05).ConclusionsFor critically ill patients with sepsis, an elevated TyG–BMI index implies a possible increased risk of AKI. The TyG–BMI index has the potential to be a valuable predictor.